BAGAN PENGERINGAN BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Efrida Basri (Jurnal Penelitian Hasil Hutan, 1990)
This paper  describes  a  kiln  drying  experiment  of  wood,  with several species  that proposed  as industrial  timber  estate. There  are  eight  species  were  investigated five of  which taken from natural forest, while the  others  are from  plantation. The  experiment  was conducted in  two stages,  quick drying  tests in an electrical oven  and  actual  drying  in two small dry kilns. Result of quick drying tests are rough kiln schedules and the  schedules  were  tested  in  the small  kilns.Drying  properties of  wood  taken  from  natural   forest  are practically   similar  to  those  of plantation stands, Tengkawang, begontoi, kuntui, damar mata kucing and jeungjing   have  the  same kiln  drying  schedule.